A review of cyberbullying detection: an overview - Nadali, Samaneh; Azmi Murad, Masrah Azrifah; Mohamad Sharef, Nurfadhlina; Mustapha, Aida; Shojaee, Somayeh (IEEE (IEEEXplore), 2013)
With the growth of Web 2.0, online communication and social networks are emerging. This alternation helps users to share their information and collaborate with each other easily. In addition, these internet services help establish new connections between persons or reinforce existing ones. However, they can also lead to misbehaviors or cyber criminal acts for example, cyberbullying. At the same time, it can make children and adolescents to use the technologies for the intention of harming another person. Due to the negative effect of cyberbullying, some techniques and methods are proposed to overcome this problem. This paper illustrates a survey covering some methods and challenges in cyberbullying. Next, we offer suggestions for continued research in this area.